ISOLATION, IDENTIFICATION, AND METAL RESISTANCE TESTING OF SOIL FUNGI (RHIZOSPHERE) FROM BANGKA TIN POST-MINING - Mutiara Darlingga; Rahmad Lingga; Andri Kurniawan (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
The ecological impacts of tin mining activities in the Bangka island is the presence of heavy metal contamination that accumulated in the environment. One of the heavy metals that was often found in post-tin mining areas is lead (Pb). Mycoremediation is a method that can be used to reduce lead pollution in post-tin mining areas. This study aimedto isolate, resistance test and identify to Pb-resistant soil fungi (rhizosphere) in the post-tin area of Bangka. The research methods included isolation, test of fungal resistance to Pb metal (Control, 150ppm, 250ppm, 350ppm, 500ppm, 1,000ppm, 5,000ppm and 10,000ppm), macroscopic and microscopic identification. The results showed that 9 isolates tested, there were 6 isolates that were resistant to Pb up to the concentration of 5,000 ppm, namely isolates I1(Rhizoctonia), I2(Penicilllium sp1), I5(Papulaspora), I6(Penicillium sp2), I7(Penicillium sp3) and I9 (Sclerotium). Three isolates of soil fungus were not resistant to Pb up to a concentration of 5,000 ppm, namely isolates I4 (Sclerotium), I8(Microsporum), and I10(Cladosporium). All isolates did not grow anymore at a concentration of 10,000 ppm of Pb.